Sociological relieve of modern human being life-sense orientations - Paulava, Katsiaryna G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The situation of existential vacuum in the sense of lifesense orientations of modern human being is studied. The orientation for dignified life is studied as ideological and personal basement. Worthy life is treated as an active official and spiritual position. The growth of interpersonal trust is possible throw the growth of friendship of equal, autonomic social beings on the level of social institutes and small groups. Social institute as a historical form of general activity impossible without human beings with their aims and social capital. Postmodern paradigm of sociology treats human being with its social capital as a real social institute, who can influence the life of social system.
Keywords: life sense orientations; existential vacuum; ideological basement; interpersonal trust; self realization